Model Pembelajaran Inkuiri dalam Meningkatkan Keterampilan Berpikir Kritis pada Mata Pelajaran IPS di Sekolah Dasar - Sofati, Siti; Ningsih, Tutuk (YASIN, 2025)
This research is motivated by the critical thinking skills that students need to prepare for the advancement of science and technology in the 21st century. To anticipate this, it is necessary to carry out various reforms and improvements in the world of education. One of them is updating and improving the learning model. This study aims to review the literature on the effectiveness of inquiry learning models in improving students' critical thinking skills in social studies subjects in elementary school. The method used in this study is a qualitative method with descriptive analysis techniques and literature studies. The results of this study show that the use of the inquiry learning model can improve students' critical thinking skills, the application of the inquiry learning model can improve students' ability to identify problems systematically and critically. Through active involvement in observing, asking, and discovering problems, students are encouraged to think sharply and develop curiosity. The conclusion of this study is that the inquiry learning model can strengthen their ability to formulate problems, as an important part of critical thinking skills. This means that the use of inquiry models is quite effective in various subjects, including social studies subjects. The implications of this research include the novelty of the findings and the impact of the applied learning model, this is expected to contribute to social studies learning in elementary schools.